2012
DOI: 10.1177/0734282912449439
|View full text |Cite
|
Sign up to set email alerts
|

Attention to Student Needs Mediates the Relationship Between Teacher Emotional Intelligence and Student Misconduct in the Classroom

Abstract: Understanding the relationship between teacher Emotional intelligence (EI) and student misconduct was the goal of this research. We hypothesized that teachers high in EI tend to establish good working relationships with students by being attentive to their students' needs. In a sample of 300 Syrian teachers, EI was assessed with the Wong and Law Emotional Intelligence scale (WLEIS; Wong & Law, 2002). Results showed that teachers' perceived EI was negatively related to student misconduct and that this relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 29 publications
1
30
0
4
Order By: Relevance
“…In general, the results of this study are in line with other authors (Di Fabio & Palazzeschi, ; Nizielski et al, ; Perry & Ball, ; Steiner & Perry, ). As Steiner and Perry () prove, individuals with more EI are able to manage and regulate their emotions, which gives them a higher quality of life and develop more stable relationships with those around them.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In general, the results of this study are in line with other authors (Di Fabio & Palazzeschi, ; Nizielski et al, ; Perry & Ball, ; Steiner & Perry, ). As Steiner and Perry () prove, individuals with more EI are able to manage and regulate their emotions, which gives them a higher quality of life and develop more stable relationships with those around them.…”
Section: Discussionsupporting
confidence: 93%
“…Studies show that management of classroom discipline reflects an essential requirement for cognitive learning and if the teacher cannot solve the problems derived from the unruly and conflicting behaviors of students, the whole process of teaching and learning will be compromised (Valente, 2015). The research results of Nizielski, Hallum, Lopes, and Schütz (2012) point out that teachers with high EI establish good working relationships with students and are attentive to their needs. In its turn, the results of the study by Anari (2012) indicate that there is a positive and significant relationship between emotional intelligence and job satisfaction.…”
mentioning
confidence: 99%
“…For example, empirical research has shown that highly emotionally intelligent teachers are better able to deal with the challenges of contemporary classroom life such as working with diverse heterogeneous classes, managing group dynamics or coping with increasing levels of teacher stress and burnout (see, e.g., Brackett et al 2010;Chan 2006;Corcoran and Tormey 2012a, 2012bJennings and Greenberg 2009). It has also been shown that such teachers tend to design more engaging lessons aimed at promoting learners' motivation (Elias and Arnold 2006;Graziano et al 2007;Nizielski et al 2012) and work at reducing rates of bullying and antisocial behaviour in their classes Levenson 1993, 1997;Richards and Gross 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Emotionally competent teachers also tend to be skilled at creating environments conducive to learning (Elias & Arnold, ; Powell & Kusuma‐Powell, ). For example, teachers’ perceived emotional competence is positively associated with supportive teacher–student relationships and negatively related to students’ challenging classroom behavior (Brackett, Reyes, Rivers, Elbertson, & Salovey, ; Jeloudar, Yunus, Roslan, & Nor, ; Nizielski, Hallum, Lopes, & Schutz, ; Perry & Ball, ; Ramana, ).…”
Section: Emotional Competencementioning
confidence: 99%